Shaping future leaders: developing an MPH leadership curriculum through problem-based learning - McHale, Aimee; Excellent, Marie Lina; Fleming, W. Oscar; Upshaw, Vaughn Mamlin (Frontiers in Public Health, 2025)
Leadership is essential to public health practice, yet few MPH programs offer structured, integrated approaches to cultivating leadership competencies. At the University of North Carolina’s Gillings School of Global Public Health, the Leadership in Practice (LIP) MPH concentration responds to this gap by embedding problem-based learning (PBL) throughout a multi-course curriculum designed to prepare students for real-world leadership challenges. Drawing on interdisciplinary faculty expertise and a constructivist pedagogical philosophy, the LIP curriculum emphasizes systems thinking, strategic decision-making, and values-based leadership development. This manuscript describes how PBL is applied across five required courses to help students synthesize technical knowledge with collaborative problem-solving and applied leadership skills. We also present alumni and employer feedback that illustrates the curriculum’s impact on workplace readiness and leadership capacity. This case study offers a model for integrating leadership development into graduate public health education and calls for broader adoption of applied, interdisciplinary pedagogies that prepare students to lead transformative change in diverse public health settings.